The Spirituality Integration in Iranian Health Education: Best Lessons for Development: spirituality integration in Iranian health education - Mehrabi, Maryam; Memaryan , Nadereh; Mohaghegh, Niloofar; Abbasi , Mahmoud (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: In the recent decade, nursing and medical schools increasingly tend to incorporate spirituality education in curriculums. This study was conducted to determine the spiritual education status and the gaps in Iranian nursing and medical schools and identify the best interventional tools to improve. Materials and Methods: It was performed a descriptive-comparative research by using an advanced search in international and national databases to collect all related materials on spiritual education. Ethical Considerations: Moral rules such as honesty and integrity in the search, analysis, reporting of the searched literature, and citation of the sources were taken into consideration. Findings: The final sample comprised 48 articles concerning spirituality integration in nursing and medical education. According to didactic various aspects, the findings subdivided into the associated subjects including; spiritual care education status in nursing and medical schools, educational patterns, interventions evaluation, and Iranian studies assessment. Conclusion: There is a leading gap regarding the spirituality integration in nursing and medical curriculums in Iran, while the religious context and the centralized management of health education in Iran can be considered as appropriate opportunities for this aim. Based on the findings, the development of a structured educational system, sensitizing educational stakeholders, and their stimulation by competitive award programs can be considered to more effective integration of spiritual training in the health curricula. *Corresponding Author: Mahmoud Abbasi; Email: dr.abbasi@sbmu.ac.ir; ORCID: https://orcid.org/0000-0002-4223-6818 Please cite this article as: Mehrabi M. Memaryan N. Mohaghegh N. Abbasi M. The Spirituality Integration in Iranian Health Education: Best Lessons for Development. Bioeth Health Law J. 2021; 1:1-9: (e16). http://doi.org/10.22037/bhl.v1i1.38167